العلاقة بين قيم بعض المتغيرات البايوكينماتيكية ودقة التهديف البعيد بوجه القدم من الداخل ومن مناطق مختلفة لدى لاعبي كرة القدم - الخشاب، زهير قاسم حمودي; إحسان، عمار علي; الأحمد، عبدالملك سليمان محمد (جامعة الموصل - كلية التربية الرياضية, 2007)
هدفت الدراسة إلى: ١-التعرف على قيم بعض المتغيرات البايوكينماتيكية في أثناء التهديف البعيد بوجه القدم من الداخل ومن مناطق مختلفة وبوجود الجدار. ٢-التعرف على العلاقة بين قيم بعض المتغيرات البايوكينماتيكية ودقة التهديف في أثناء أداء التهديف البعيد بوجه القدم من الداخل ومن الكرات الثابتة ومن مناطق مختلفة وبوجود الجدار - واستخدم الباحثون المنهج الوصفي وتكونت عينة البحث من (١٩) لاعبا (١٥) استخدموا لتصميم الاختبار و (٤) لاعبين لتجربة البحث الرئيسية، إذ يقوم كل لاعب من اللاعبين الأربعة بأداء ستة محاولات تهديف على الهدف في كل جهة من الجهات الثلاثة وتسجيل له أفضل محاولة، وتم تحديد موقع ألة التصوير من نقطة التهديف وارتفاعها وأجريت التجربة الاستطلاعية وبعدها أجريت التجربة الرئيسية على عينة البحث ثم عولجت البيانات إحصائيا باستخدام الوسط الحسابي والانحراف المعياري ومعامل الارتباط البسيط (بيرسون) كوسائل إحصائية للبحث. واستنتج الباحثون ما يأتي: ١-وجود ارتباط موجب بين زاوية الكاحل للرجل الضاربة لمرحلة الاصطدام من الجهة اليمنى والسرعة الزاوية للجسم من الجهة الوسطى. ٢-عدم وجود ارتباط معنوي بين مرحلتي الامتصاص والضرب لمتغيرات البحث. وأوصى الباحثون بما يأتي: ١-التأكيد على دراسة المتغيرات البايوكينماتيكية التي حصلنا من خلالها على نتائج إيجابية للاستفادة منها في عمليات التدريب وتعلم كرة القدم. ٢-تقويم هذه المهارة خلال مراحل البرنامج التدريبي لغرض معرفة التقدم في درجة الدقة عند أدائها. This study is aimed at : 1. Obtaining some biokinmatic variables during the precise, distance instep shooting from various area and in front of the defensive wall. 2. Knowing the relationship between some biokinmatic variables and the precise, distant instep shooting from various areas. It is worth bearing in mind that that the researcher has used the descriptive method in this research The research sample is made up of (19) players (15) of whom have been used to design the test whereas the remaining (4) have been used within the research experiment where each of the four players has made (6) shooting attempts from each of the three directions and has been given (5)marks as a maximum and (zero)as a minimum and all the shooting attempts conducted have been filmed and the best one has been analyzed , furthermore, the camera position and its height have been pinpointed accurately in relation to the shooting point , then the surveying test has been conducted and followed by the main test of the research sample before processing the data statistically by using the Arithmetic means, standard deviation and simple correlation coefficient (Pearson) as research statistical methods. The researchers have reached to the following conclusions: 1- There has been a positive correlation between the following two variables (The ankle angle of the striking leg during the collision stage in the right direction and the angular velocity of the body in the middle ). 2- The absence of any significant correlation relationship of the absorption and striking stages of the research variables . Finally the researchers has made the following recommendations: The emphasis on the study of the biokinematic variables the researcher have obtained from their research work in order to utilize them in soccer teaching and training processes.
Keywords: المتغيرات البايوكينماتيكية -- التهديف البعيد -- وجه القدم -- لاعبو كرة القدم -- الاختبارات و المقاييس